Peculiarities of Flexibility Development in Middle Schoolers - Солодовникова, М. В. (Physical Education Theory and Methodology, 2015)
The paper objective is to define the peculiarities of flexibility development in middle schoolers. To solve the tasks set, the study used the following research methods: theoretical analysis and collation of scientific and methodological literature; pedagogical testing, methods of mathematical statistics. Research results. The testing analysis showed statistically unreliable deviations in the results displayed by the fifth-, sixth- and seventh-grade girls in the following tests: “Rotation in the shoulder joint with a staff”, “Backbend from the lying position”, “Forward bend from the sitting position” (p > 0.05). The fifth-, sixth- and seventh-grade girls show improvement in their statistically significant results (p < 0.05) in the following tests: “Raise up from the lying position to the sitting position in 30 seconds”, “Bending and unbending of arms in the lying position”. The testing analysis showed a statistically significant deterioration in the results displayed by the fifth-, sixth- and seventh-grade boys in the following tests: “Rotation in the shoulder joint with a staff”, “Backbend from the lying position” (p < 0.05). The fifth-, sixth- and seventh-grade boys show improvement in their statistically significant results (p < 0.05) in the test " Raise up from the lying position to the sitting position in 30 seconds”, and an improving tendency in the results in the test “Bending and unbending of arms in the lying position”. Conclusions. The informative indicators of flexibility and strength readiness of the 5th-7th-grade boys are “Rotation in the shoulder joint with a staff”, “Backbend from the lying position” and “Raise up from the lying position to the sitting position in 30 seconds”. The informative indicators of strength readiness of the 5th-7th-grade girls are “Raise up from the lying position to the sitting position in 30 seconds”, “Bending and unbending of arms in the lying position”. The flexibility testing results for the fifth-grade pupils vary in the level from average high, and the strength testing results — from below average to average. The flexibility testing results for the sixth-grade pupils vary in the level from below average to average, the strength testing results being the same. The flexibility results of the seventh-grade boys vary in the level from low to average, and the strength skills results — from above average to high.